The treatment of enzootic calf pneumonia wit tiamutin - Veysi ASLAN (Eurasian Journal of Veterinary Sciences)
This investigation has been made in Konya from 1986 - 1987'in winter season ori 50 calves with enzootic pneumonia. In investigation, the most affected calves in the infected herds were chosen. Tiamutin was injected (1 ml/10 kg) intramuscularly to each infected calf for three consecutive days. All of the calves recovered by this treatment.